The use of multidimensional space in the graph-analytical description of multifactorial events and processes - Mahmudov Maqsud Sheralievich (International Journal on Orange Technologies, 2020)
The article discusses the grapho-analytical properties of straight lines in a special case applied in three-dimensional space in order to automatically line the plastic function used in the design of shell surfaces.